2018
DOI: 10.2478/acm-2018-0010
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Low-level radiofrequency electromagnetic fields in the human environment

Abstract: In recent years there has been an increase in development of electromagnetic (EM) technology in the telecommunication industry, resulting in an increase in human non-ionizing exposure. This fact has initiated a number of scientific studies on possible health effects of EM fields on human organism. Totally four representative microenvironments were investigated for RF EM fields distribution, namely: city center, residential area, rural area, and extra-village area. Each microenvironment was measured 20 times in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…It is most likely that an excessive exposure to mobile devices working at 4G or 5G networks becomes more dangerous for the biological system. Study group Misek et al [23] described the measurement of RF EMF in the living environment. They found that, the distribution of E EMF in the city center was 0.16±0.02 V/m for 3G, 0.048±0.005 V/m for 4G and 9.81±3.66 * 10 -3 V/m for WiFi.…”
Section: Discussionmentioning
confidence: 99%
“…It is most likely that an excessive exposure to mobile devices working at 4G or 5G networks becomes more dangerous for the biological system. Study group Misek et al [23] described the measurement of RF EMF in the living environment. They found that, the distribution of E EMF in the city center was 0.16±0.02 V/m for 3G, 0.048±0.005 V/m for 4G and 9.81±3.66 * 10 -3 V/m for WiFi.…”
Section: Discussionmentioning
confidence: 99%
“…The effects include an increased risk of cancer, cellular stress, increased levels of harmful free radicals, genetic damage, structural and functional changes in the reproductive system, learning and memory deficits, neurological disorders, and a negative impact on human well-being (8). The study by points the need to monitor each new base transceiver station which is a source of low energy but permanent whole-body exposure (9). Blank and Goodman (2009) argue that EMF has the ability to act on human cells and DNA and the cells respond by a stress response (11).…”
Section: Introductionmentioning
confidence: 99%
“…It can be mentioned that all of the indicated studies in our survey, where intensities of electric field were measured, did not exceed the allowed ICNIRP limits. However, according to limits given by the BioInitiative Report they were exceeded in some of our studies [22,29]. According to the limits set by the BioInitiative Report [38], intensities of electric field above 0.1 -0.15 V/m for the frequency range 400 - 2000 MHz are considered as a risky value, whereas for ICNIRP it was 58.354 V/m (limits of ICNIRP are valid for Slovakia, too).…”
Section: Discussionmentioning
confidence: 85%